Assessing mitral regurgitation in the prediction of clinical outcome after cardiac resynchronization therapy - Upadhyay, Gaurav A.; Chatterjee, Neal A.; Kandala, Jagdesh; Friedman, Daniel J.; Park, Mi-Young; Tabtabai, Sara R.; Hung, Judy; Singh, Jagmeet P. (Heart rhythm, 2015)
Cardiac resynchronization therapy (CRT) has been shown to reduce mitral regurgitation (MR), although the clinical impact of this improvement remains uncertain. We sought to evaluate the impact of MR improvement on clinical outcome after CRT and to assess predictors and mechanism for change in MR. This was a cohort study of patients undergoing CRT for conventional indications with baseline and follow-up echocardiography (at 6 months). MR severity was classified into 4 grades. The primary end point was time to all-cause death or time to first heart failure (HF) hospitalization assessed at 3 years. A total of 439 patients were included: median age was 70.2 years, 90 (20.5%) were women, 255 (58.1%) with ischemic cardiomyopathy, and mean QRS width was 162 ms. Worsening severity of baseline MR was independently predictive of HF or all-cause mortality (hazard ratio 1.33; 95% confidence interval 1.01–1.75; P = .042). Reduction in MR after CRT was significantly associated with lower HF hospitalization and improved survival (hazard ratio 0.65; 95% confidence interval 0.49–0.85; P = .002). Degree of baseline MR and longer surface QRS to left ventricular lead time were significant predictors of MR change. Patients with MR reduction exhibited lower mitral valve tenting area (P < .001) and coaptation height (P < .001) than those with stable or worsening MR, suggestive of improved ventricular geometry as a mechanism for change in MR. Degree of baseline MR and change in MR after CRT predicted all-cause mortality and HF hospitalization at 3 years. Longer surface QRS to left ventricular lead time at implant may be a means to target MR improvement.